Implementation of expressions using Python in stimulated luminescence analysis. (June 2022) - Prevezanou, K.; Kioselaki, G.; Tsoutsoumanos, E.; Konstantinidis, P.G.; Polymeris, G.S.; Pagonis, V.; Kitis, G.
Abstract: In Thermoluminescence (TL) and Optically Stimulated Luminescence (OSL), the study of complex experimental TL glow curves and OSL signal processing, also known as deconvolution, was revolutionized by using a single, analytic master equation described by Lambert W function. This latter equation has been also adopted for the case of dose response fitting. The present study exploits the utilization of Lambert W function in Python programming environment. These analytic expressions are based on One Trap-One Recombination center (OTOR) and Two Traps-One Recombination center (TTOR) models. Python scripts, with corresponding software flowchart being described in general, are created to deconvolve TL, LM-OSL, CW-OSL as well as to fit dose response experimental data. The calculated results are in agreement with those of the existing literature. Also, all scripts are free and available in GitHub to the research community for downloading. Highlights: Python scripts for the deconvolution of TL glow and OSL decay curves. Dose response curves analyzed with Python scripts based on OTOR and TTOR models. Calculated results are in accordance with the literature. Deconvolution and dose response scripts are available in GitHub.